A novel QCA shuffle-exchange network architecture with multicast and broadcast communication capabilities. (November 2019) - Abutaleb, M.M.
Abstract: In large-scale computing systems, interconnection networks are used to provide reliable and fast on-chip communication between processing elements and embedded modules in order to perform complex core tasks. These networks can be formed in different architectures that are built using multiple stages of switching elements and connecting links. Shuffle-exchange network (SEN) is broadly used as an interconnection architecture with unique input-output paths, simple configuration, and latency reduction. In this paper, a new four-function switching element (SE) with two inputs and two outputs is proposed and designed in Quantum-dot Cellular Automata (QCA) nanotechnology. It can be configured to form all possible 1 × 2 and 2 × 2 interconnections. Consequently, the proposed switch is utilized to implement the nanoscale interconnection structure of multi-stage SEN with multicast and broadcast capabilities for the first time. It can perform "One-to-One", "One-to-Multiple", and "One-to-All" communications between various components in computing systems. In order to demonstrate the functionality and capabilities of the proposed QCA-based SEN architecture, performance is evaluated and analyzed. Furthermore, its hardware complexity is examined and compared with existing QCA-based network architectures.